BAHAYA PAPARAN PESTISIDA TERHADAP KESEHATAN REPRODUKSI - Indrayanti; Latip, Abdul; Rahayu, Ari Tri; Ernawati, Masfuah (Poltekkes Kemenkes Mataram, 2025)
Pesticides are one of the toxic and dangerous chemicals (B3) and are persistent organic pollutants. If you use unsafe pesticides, it can affect a person's health. WHO estimates that around one million suffer pesticide poisoning every year. 11,000 would have fatal consequences. The mechanism of action of pesticides in the human body is to influence the work of enzymes and hormones and can damage tissue by inducing the production of serotonin and histamine. Pesticides are cytotoxic, carcinogenic and mutagenic for health and can be toxic to the reproductive system. Toxins in the reproductive system that are metabolized will enter the ovaries and cause the cells in the ovaries to become damaged. Pesticides can also cause decreased fertility, hormonal imbalance, damage to the germinal epithelium, genetic changes in men, exposure during the preconception period resulting in an increased risk of spontaneous abortion, slow fetal growth and premature birth. The aim is to increase the knowledge and skills of Village Health Cadres regarding the dangers of pesticide exposure to reproductive health The methods used are lectures, demonstrations, pre and post tests. Pre and post with 20 questions about the dangers of pesticide exposure for health. The participants were 35 health cadres from Mojodeso Village, Kapas District, Bojonegoro Regency; the results of the most 18 (51.4%) training participants' knowledge during the post-test were in the very good category. All participants (100%) were able to provide counseling to 75 families in the good category